Formulating an Islamic Counseling Model for Strengthening Religious Identity Among Madrasah Students - Zul Arwan; Hasnil Aida; Rahmad Aji Widiono (Al-Fikru: Jurnal Ilmiah, 2026)
Religious identity has become an important issue among adolescents due to technological advancement, digital media, and social changes that influence their values, behaviors, and spiritual commitment. Although Islamic counseling has been implemented in educational settings, studies formulating a counseling model to strengthen the religious identity of madrasah students remain limited. This study aims to identify the characteristics of students' religious identity, examine the educational and spiritual factors influencing its development, and formulate an Islamic counseling model. A qualitative single case study was conducted at MTs Al Washliyah Gedung Johor Medan. Data were collected through observations, semi-structured interviews, and document analysis involving teachers, the head of the madrasah, and selected students. The findings show that religious identity is influenced by teacher role modeling, spiritual practices, family support, peer interaction, and digital media exposure. The proposed model comprises four stages: comprehensive identification, integrated spiritual reinforcement, character formation, and continuous mentoring and evaluation. This model offers theoretical and practical contributions to strengthening religious identity among madrasah students.